Alcohol consumption, smoking and lifestyle characteristics for Japanese patients with chronic obstructive pulmonary disease - Hirayama, Fumi (Curtin University, 2008)
This thesis investigated lifestyle characteristics including cigarette smoking, alcohol consumption, dietary supplements intake, physical activity, and urinary incontinence status for Japanese patients with chronic obstructive pulmonary disease (COPD). Field studies were conducted in the middle of Japan. The study was conducted using a cross-sectional survey and all patients were recruited from the outpatient departments of six hospitals in three districts/prefectures, namely, Aichi, Gifu, and Kyoto. Three hundred referred COPD patients diagnosed by respiratory physicians were recruited in 2006. Inclusion criteria were (i) aged between 50 and 75 years; and (ii) had COPD as the primary functionally limiting illness which was diagnosed within the past four years. Diagnosis of COPD was confirmed by spirometry with FEV1/FVC < 70%, where FEV1 = forced expiratory volume in one second and FVC = forced vital capacity. A structured questionnaire was administered to collect information on lifestyle characteristics. All interviews, averaging 40 minutes, took place in the hospital outpatient departments. Clinical characteristics, height, weight and presence of any co-morbidity (e.g. diabetes, hypertension, cardiovascular disease), were retrieved from medical records.A total of 278 eligible participants (244 men and 34 women) were available for analysis. The majority were men (88%) with mean age 66.5 (SD 6.7) years and mean body mass index (BMI) 21.9 (SD 3.6). Most of them were married (84%), had high school or below education (80%) and retired (55%). In relation to cigarette smoking, 62 (53 male and 9 female) participants (22.5%) were current smokers of whom the great majority (89%) smoked daily. Only six (2.1%) participants were never smokers. The prevalence of smoking by time from diagnosis was: 24.5% (< 1 year), 20.6% (1-2 years), and 18.9% (2-4 years). Continuous smoking was inversely associated with age (odds ratio (OR) = 0.94, 95% confidence interval (CI) 0.90-0.98), BMI (OR = 0.88, 95% CI 0.80-0.97) and disease severity vii (OR = 0.29, 95% CI 0.12-0.74 for severe COPD and OR = 0.29, 95% CI 0.09-0.92 for very severe COPD). For alcohol consumption, 158 (150 male and 8 female) patients (56.8%) drank alcohol regularly on at least a monthly basis, the majority of them (73.4%) being daily drinkers. Beer was the most preferred alcoholic beverage drank (30.9%). Alcohol intake appeared to be positively associated with the habit of adding soy sauce to foods, whereas dyspnoea of patients posed significant limitations for them to drink alcoholic beverages.Also, female patients tended to have lower alcohol consumption levels than male patients. Regarding dietary supplements, 117 (101 male and 16 female) participants (42.1%) were dietary supplement users, but the prevalence for female patients (47.1%) was higher than male patients (41.4%). Younger patients (≤ 60 years) and those with severe COPD had relatively low proportion of users (27.3% and 28.9%, respectively). Dietary supplementation was found to be affected by age (p = 0.04), COPD severity (p = 0.03) and presence of co-morbidity (p = 0.03). Older patients over 60 years were more likely to take dietary supplements (OR = 2.44, 95% CI 1.03-5.80), whereas severe COPD patients (OR = 0.41, 95% CI 0.18-0.95) and those with a co-morbidity (OR = 0.54, 95% CI 0.32-0.94) tended not to use. With respect to physical activity of COPD patients, 198 (175 male and 23 female) of them (77%) participated in physical activities on at least weekly basis, but only 22% and 4% engaged in moderate and vigorous activities, respectively. Over 2/3 of them walked at least weekly. Regression analysis showed that perceived life-long physical activity involvement appeared to be positively associated with total physical activity, whereas patients with very severe COPD tended to have significantly lower total physical activity levels.Besides COPD severity, both age and smoking exhibited a negative impact on walking. It is evident that walking activities decreased among very severe patients, current smokers and those in advanced age. The prevalence of urinary incontinence was 12.6% (10% for men and 32% for women). The most common occurrence of urine loss was before reaching the toilet (54%) followed by coughing/sneezing (23%). While urge incontinence was reported viii by 63% of male incontinent patients, 82% of female incontinent patients experienced stress incontinence. Incontinence was more likely among female patients (OR = 8.7, 95% CI 3.2-23.4) and older patients over 70 years (OR = 2.3, 95% CI 1.0-5.2). COPD severity was also found to be a significant factor (p = 0.007), with very severe patients at slightly higher risk of urinary incontinence (OR = 1.1, 95% CI 0.3-3.5) than mild COPD patients, though the relationship appeared not to be linear across the severity classifications. It is alarming to find mild and moderate COPD patients continue to smoke. The implementation of a co-ordinated tobacco control program immediately post diagnosis is needed for the effective pulmonary rehabilitation of COPD patients. The high alcohol consumption by COPD patients is also alarming. Alcohol control programs targeting male patients should be promoted during pulmonary rehabilitation in order to minimise the harm due to excessive drinking. Dietary supplements are popular for patients with COPD especially among older patients.The findings are important to clinical trials and experimental interventions advocating nutritional supplementation therapy for pulmonary rehabilitation. Patients with COPD had lower physical activity levels than the general elderly population. Older patients with very severe COPD and those who currently smoke should be targeted for intervention and encouraged to increase their participation in physical activity so as to maintain their health and well being. The high prevalence yet underreporting of urinary incontinence suggested that education and regular assessment are needed after COPD diagnosis. Appropriate exercise and treatment tailored for the specific type of incontinence incurred should be incorporated within the rehabilitation program of COPD patients. To maintain a healthy lifestyle and to achieve optimal outcomes during the pulmonary rehabilitation of COPD patients, the identified factors should be taken into consideration and health awareness programs should be promoted in conjunction with respiratory physicians and allied health professionals.